Awareness of Socio-Scientific Issues among the Higher-Secondary Students - Singh, Sunita; Singh, Sharda (SCHOOL SCIENCE, 2017)
Science and society are interdependent and all aspects of science are inseparable from the society from which they arise. Today, society is continuously confronting numerous issues concerned with health and environment like cloning, ozone depletion, etc. These issues emerged from the interactions of science and society hence it is important to create awareness towards socio-scientific issues among students. The main aim of present paper is to study the awareness of socio-scientific issues among the higher secondary students. For this purposes researchers used self-developed ‘Awareness of socio scientific issues’ tool. This tool was administered on 654 higher secondary school students. It was found that majority of students are not aware of socio-scientific issues. In addition, it was also found that awareness of socio scientific issues among students is influenced by gender, board, academic discipline whereas it is not influenced by locality of students. Findings of research urge the need to develop suitable syllabus, textbook and teaching strategies so that it increases the awareness among students towards socio scientific issues